2018
DOI: 10.7717/peerj.4280
|View full text |Cite
|
Sign up to set email alerts
|

Moving to 3D: relationships between coral planar area, surface area and volume

Abstract: Coral reefs are a valuable and vulnerable marine ecosystem. The structure of coral reefs influences their health and ability to fulfill ecosystem functions and services. However, monitoring reef corals largely relies on 1D or 2D estimates of coral cover and abundance that overlook change in ecologically significant aspects of the reefs because they do not incorporate vertical or volumetric information. This study explores the relationship between 2D and 3D metrics of coral size. We show that surface area and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 53 publications
1
67
0
Order By: Relevance
“…Most of the colony volume is non‐living aragonite skeleton that requires a large proportion of the colony's energy to produce (Osinga et al, ). Planar area is the two‐dimensional area of a colony when viewed from above and is a low‐cost measure of colony size commonly used in field studies, and recent work has shown that planar area and growth form can estimate surface area and volume accurately (House et al, ). However, these traits alone cannot capture how surface area and volume are distributed.…”
Section: Morphological Traits Linked To Performance Function and Resmentioning
confidence: 99%
“…Most of the colony volume is non‐living aragonite skeleton that requires a large proportion of the colony's energy to produce (Osinga et al, ). Planar area is the two‐dimensional area of a colony when viewed from above and is a low‐cost measure of colony size commonly used in field studies, and recent work has shown that planar area and growth form can estimate surface area and volume accurately (House et al, ). However, these traits alone cannot capture how surface area and volume are distributed.…”
Section: Morphological Traits Linked To Performance Function and Resmentioning
confidence: 99%
“…Developing a quantitative framework is challenging for colonial organisms because they have geometrically complex forms, high intraspecific and interspecific variation in shape, and lack readily identifiable landmarks for comparative analysis. However, new technologies such as CT and laser scanning make it possible to accurately capture the diversity of shapes exhibited by colonial organisms (Lavy et al 2015;House et al 2018). Here, using reef corals as a study system, we develop a morphological schema using quantitative, three-dimensional shape variables.…”
Section: Introductionmentioning
confidence: 99%
“…However, while these results highlight differences between growth forms across a range of processes, they are unable to directly assess process-based hypotheses for the observed differences, nor can the results be generalised to other growth forms or taxa with similar morphological adaptations but different overall morphology (e.g., sponges, hydrozoans, algae, plants, etc). As such, recent studies have begun to explore techniques for quantifying and comparing the three-dimensional shape of corals (Lavy et al 2015;Reichert et al 2017;Bythell, Pan, and Lee 2001;House et al 2018). We build on this work to develop a quantitative schema for coral morphology via variables that capture shape variation.…”
Section: Introductionmentioning
confidence: 99%
“…When geometrically corrected, these products can be used to detect centimeter changes in volume and surface area [17][18][19][20][21]. Scientists have used SfM models to accurately estimate a variety of ecological indicators such as linear rugosity, surface complexity, slope, and fractal dimension [22][23][24]. In an effort to design a more repeatable and consistent platform to collect data for SfM monitoring of coral reefs and other benthic habitats, we explore the use of recent advancements in open source Global Positioning System (GPS)-guided drone and camera technology to design and test a low-cost and transportable small unmanned surface vehicle (sUSV).…”
Section: Introductionmentioning
confidence: 99%